DIGITALISATION IN VOCATIONAL EDUCATION: ENHANCING SKILLS AND JOB READINESS IN DEVELOPING COUNTRIES - Sri Utami; Eka Haryati Yuliany; Michael Gerits Kriswanto Remetwa (CV. ADIBA AISHA AMIRA, 2025)
Digitalisation in vocational education plays an important role in improving skills and work readiness in developing countries. Through the application of digital technology, access to more varied and quality learning resources becomes easier, and more interactive learning methods can be implemented. This approach not only strengthens learners' theoretical understanding but also provides practical experience needed in the industrialised world. The integration of technology tools and applications used in real industries into the vocational education curriculum ensures learners' readiness to face the evolving world of work. Technology-based training such as virtual simulations and e-learning platforms contribute significantly to learners' adaptability to technological changes and industry developments. In addition, digitalisation opens up wider collaboration opportunities between educational institutions, industry and government, creating a supportive ecosystem for innovation and knowledge transfer. Through technology-based internship programmes and partnerships with technology companies, learners can gain relevant work experience and direct feedback from the industry. Overall, digitalisation in vocational education strengthens the link between education and the world of work, preparing learners with the necessary skills and competencies to compete in the global job market.